PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 031 TANJUNG SARI KECAMATAN PUJUD ROHIL - Ina Fauziah; Mahmud Alpusari; Lazim. N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study in the background backs by poor learning outcomes IPS 031 students of class V SDN Tanjung Sari subdistrict Pujuddengan class average 67.4%. While the value of minimum criteria for completeness (KKM) IPS is 70. Among the students who totaled 25 people, only 10 students were reached KKM with classical completeness 40%). This research is a classroom action research (CAR) conducted aims to improve learning outcomes IPS 031 students of class V SDN Tanjung Sari Pujud District to the Implementation Model Quantum Teaching To Improve Learning Outcomes IPS Student Class V SDN 031 Tanjung Sari Pujud District of Rokan Hilir. Formulation of the problem: whether the Application Model of Quantum Teaching To Improve Learning Outcomes IPS Student Class V SDN 031 Tanjung Sari Pujud District of Rokan Hilir. This study was conducted on 21 March 2016 to 11 April 2016 to 2 cycles. The subjects were students of class V SDN 031 Tanjung Sari subdistrict Pujudyang total 25 people were used as the data source. Data collection instrument in this paper is a sheet activities of teachers and students and learning outcomes. Activities teachers during the learning process by using the application of Quantum Teaching Model in the first cycle with the first meeting 50% Less categories, the first cycle of the second meeting of 58.33% with a category, please. In the second cycle the first meeting of 70.83% with good category, the second cycle II meeting of 87.50% with a very good category. Increased. Activities of students during the learning process by using the application of Quantum Teaching Model in the first cycle with the first meeting 41.6% Less categories, the first cycle of the second meeting of 54.16% with a category, please. Increased. In the second cycle the first meeting of 66.66% with good category. In the second cycle II meeting of 83.33% with a Very Good category has increased. Application of Model Quantum Teaching in the learning process can improve student learning outcomes IPS from basic score average (67.4) to the average UH I (69.6) base score (48.88%) to UH II to the average (75.8) experienced increase.Keywords: Model Quantum Teaching, Learning Outcomes IPS2